The current state of the problem of cervical screening - Shumilina , Tetiana; Korchynska , Oksana; Khashcha , Ivan; Mitsoda , Roman (The Ukrainian Scientific Medical Youth Journal, 2024)
the article summarizes the issue of prevention of cervical cancer - the most common disease associated with the human papillomavirus (HPV). The main goal of this study is to generalize the etiology of cervical cancer, to note unique opportunities for its prevention, as well as to develop screening tests for HPV as one of the most effective strategies. Explore how current HPV diagnostics detect E6/E7 DNA or mRNA in cervical/vaginal specimens using molecular technologies. To find out whether HPV screening tests are more sensitive than cytology or visual examination with acetic acid as the primary screening method, and even more clinically valuable for detecting subtle cytological changes as a hybrid test. Through a detailed study of literature sources, their systematization and approaches to solving the problem, it was found that technical and laboratory capabilities are very limited in underserved places, so women have to travel long distances and make some efforts to prevent and treat cervical cancer. The relevance of the study of this pathology lies in the fact that cervical cancer is a serious public health problem and is the fourth most common cancer in women worldwide, accounting for about 604,000 new cases every year. And the practical implementation of an HPV screening program can face many problems, and measures must be taken to overcome these problems without compromising the detection of the disease. These measures could include reducing the frequency of screening using the WHO global strategy to offer HPV screening tests at ages 35 and 45, implementing high-throughput testing technology, and improving access to vaginal HPV screening tests for women in remote areas. Improving informational education for those who do not want to undergo a gynecological examination. Another important strategy is to implement a see-and-treat approach using a healthcare delivery platform that requires limited laboratory technician skills. In addition, the development and large-scale implementation of more specific HPV testing technologies that are much cheaper and easier to use in a non-laboratory setting than currently available options should be a priority for underserved facilities. At the same time, there is a need to develop and initiate implementation of an affordable and readily available intermediate or secondary test with optimal specificity to triage or separate clinically insignificant HPV infections that do not require colposcopy. The results of this study may be of interest to primary care physicians, gynecologists, oncologists, and therapists.